Investigation of chemical etching on flow in channel - Kan, Kah Yee (Nanyang Technological University, 2020)
With dwindling energy sources, energy-efficient processes have been an important focus in research. One significant source of energy loss in processes is frictional drag in channel flow. Superhydrophobic surfaces have been shown to be effective in reducing friction drag, thus, many methods of fabricating such surfaces have been developed. Some methods require expensive equipment, environmental concerns or severe conditions, which make them unsuitable for large-scale production. This project focuses on chemical etching due to its low cost, fast production time and ability to control the fabricated surface morphology. AZ91D magnesium alloy is used as the material in this project due to its light weight and other unique properties. A two-step chemical etching method using dilute sulfuric acid, copper (II) sulfate and ethanolic stearic acid is used to fabricate the superhydrophobic surfaces. This study aimed to explore the effect of various parameters on the quality of the superhydrophobic surface and to determine an optimal combination of parameters. Contact angle and surface morphology are used to characterise the quality of the fabricated surface. Preliminary pressure drop experiments are also conducted to explore the drag-reducing properties of the fabricated superhydrophobic surfaces. The project found that using 0.075M of sulfuric acid for an etching time of 4 minutes, then etching with 0.2M copper (II) sulfate for 0.5 minutes and passivating in 0.05M ethanolic stearic acid for 30 minutes produced the most optimal surface with an average contact angle of 164.98°. Three features of surface morphology that optimised superhydrophobicity were also determined. Preliminary pressure drop experiments also showed that the fabricated surfaces could reduce frictional drag.